Effects of exercise treatment on functional outcome parameters in mid-portion achilles tendinopathy: a systematic review - Kim, Myoung-Hwee; Lin, Chiao-I; Henschke, Jakob; Quarmby, Andrew; Engel, Tilman; Cassel, Michael (Frontiers in Sports and Active Living, 2023)
Exercise interventions are evident in the treatment of mid-portion Achilles tendinopathy (AT). However, there is still a lack of knowledge concerning the effect of different exercise treatments on improving a specific function (e.g., strength) in this population. Thus, this study aimed to systematically review the effect of exercise treatments on different functional outcomes in mid-portion AT. An electronic database of Pubmed, Web of Science, and Cochrane Central Register of Controlled Trials were searched from inception to 21 February 2023. Studies that investigated changes in plantar flexor function with exercise treatments were considered in mid-portion AT. Only randomized controlled trials (RCTs) and clinical controlled trials (CCTs) were included. Functional outcomes were classified by kinetic (e.g., strength), kinematic [e.g., ankle range of motion (ROM)], and sensorimotor (e.g., balance index) parameters. The types of exercise treatments were classified into eccentric, concentric, and combined (eccentric plus concentric) training modes. Quality assessment was appraised using the Physiotherapy Evidence Database scale for RCTs, and the Joanna Briggs Institute scale for CCTs. The search yielded 2,260 records, and a total of ten studies were included. Due to the heterogeneity of the included studies, a qualitative synthesis was performed. Eccentric training led to improvements in power outcomes (e.g., height of countermovement jump), and in strength outcomes (e.g., peak torque). Concentric training regimens showed moderate enhanced power outcomes. Moreover, one high-quality study showed an improvement in the balance index by eccentric training, whereas the application of concentric training did not. Combined training modalities did not lead to improvements in strength and power outcomes. Plantarflexion and dorsiflexion ROM measures did not show relevant changes by the exercise treatments. In conclusion, eccentric training is evident in improving strength outcomes in AT patients. Moreover, it shows moderate evidence improvements in power and the sensorimotor parameter “balance index”. Concentric training presents moderate evidence in the power outcomes and can therefore be considered as an alternative to improve this function. Kinematic analysis of plantarflexion and dorsiflexion ROM might not be useful in AT people. This study expands the knowledge what types of exercise regimes should be considered to improve the functional outcomes in AT.